A Low-cost, Practical Method for Increasing Smokers’ Interest in Smoking Cessation Programs - McDonald, Paul W. (Can J Public Health, 2004)
BACKGROUND: Low participation rates reduce the public health impact of smoking cessation programs. Two barriers for improving participation are the cost of media campaigns and the proportion of smokers motivated to quit smoking. The objective of this study was to examine the feasibility of using classified newspaper ads and messages aimed at each stage of change to enhance participation in smoking cessation programs. METHODS: Three classified ads were run concurrently in a local daily newspaper for five consecutive days. The ads were designed to engage smokers in each of Prochaska’s five stages of change. Each ad invited smokers or former smokers to call the local health department to participate in a paid focus group to design a new health department program. RESULTS: Calls were received from 181 eligible smokers, including 124 who provided data for the study. Thirty-seven, 34, and 29 percent of smoking respondents were in precontemplation, contemplation and preparation respectively. Half of ex-smokers were in the action stage. Ads cost $174 (Cdn), thus the cost per recruit was less than a dollar. CONCLUSION: Classified ads can recruit smokers from all stages of change. Compared to traditional mass media, classified ads may also be a highly cost-efficient promotional strategy. Results provide justification for further research.